A review of operational control strategies in water supply systems for energy and cost efficiency. (April 2023) - Reis, Ana L.; Lopes, Marta A.R.; Andrade-Campos, A.; Henggeler Antunes, Carlos
Abstract: Water supply systems (WSS) are intensive energy demanding infrastructures relying on water storage tanks and pumping systems for delivering water to consumers which face challenges such as increasing water demand, aging infrastructure and rising energy prices. The energy transition, namely in the power sector, offers opportunities for water utilities to provide demand-side management with mutual benefits for both sectors. Current investments in renewable energy sources for self-consumption contribute to reduce the impact of energy price fluctuations on water utilities' bills. These opportunities increase the available resources to be managed, making the efficient operational management of WSS a complex task. A systematization of control strategies that can be used in this context are lacking in the literature. The aim of this work is to review and systematize operational control strategies to reduce energy and costs in WSS by analyzing existing literature. The participation in demand response mechanisms, adoption of energy efficiency measures, and utilization of renewable energy sources are explored. The main original contribution of this work relies on investigating control strategies considering the opportunities fostered within the energy transition for water utilities by addressing the WSS resources management from an integrated (supply and demand) perspective and the importance of decision support tools to drive this integration. Major research gaps identified include the need for the development of appropriate tools to support real-time decision making in WSS operation. Research on optimization techniques applied to complex water networks and extended periods is still scarce, which opens promising research avenues. Highlights: The ongoing energy transition offers savings opportunities for water utilities through DSM. Optimization tools enable more efficient real-time operation of WSS. Decision support tools are key for the integrated management of resources in WSS. Energy cost-optimizing operational control strategies for WSS management are analyzed.